Klotho no câncer : uma revisão sistemática - COSTA, Jucileide Mota (2023)
Introduction and objective: The Klotho protein, encoded by the KL gene, is part of the FGF-Klotho endocrine system and plays a role in the pathophysiology of agerelated disorders, including cancer. Klotho is considered a tumor suppressor and has potential for treating cancer. It has been found to reduce the proliferation of cancer cells and induce apoptosis in several types of cancer. The molecular mechanism underlying the tumor suppressive effect of Klotho is not well understood. Klotho forms a complex with FGFRs and is required for the high affinity binding of FGFs to their receptors. It is expressed in various tissues and organs, with highest levels in the kidney. Klotho interacts with several members of the Wnt family and may play a role in aging. Alterations in Wnt signaling are implicated in cancer development and progression. This dissertation discusses the role of Klotho proteins in various types of cancer and their potential use as diagnostic and prognostic markers. Methodology: This is a systematic review, which analyzed articles published between 2012 and 2022, according to the Preferred Reporting Items for Systematic Reviews and Metaanalyses (PRISMA). The search strategy was carried out in three databases: PubMed, Scielo and ScienceDirect, using the keywords "cancer AND Klotho", accessed in April 2023. The search resulted in 836 articles, 401 of which were duplicates. the inclusion and exclusion criteria, 26 articles were part of this systematic review. Results: Among the 26 articles selected, 21 dealt with αKlotho, 5 with βKlotho and only 3 with γKlotho, one article studying α and βKlotho and another studying all three proteins. αKlotho was found to be consistently associated with improved prognosis and may be useful for estimating cancer patient survival. αKlotho appears to act as a tumor suppressor and its down-regulation has been associated with aggressive tumor phenotypes and worse prognosis. Elevated γKlotho levels are associated with cancer aggressiveness and poor prognosis, and may be useful in predicting patient survival and response to therapy. βKlotho shows mixed results. Conclusion: While αKlotho was associated with a better patient prognosis, γKlotho was associated with increased cancer aggressiveness, and βKlotho had mixed results. It is essential to accurately identify tumor subtypes and Klotho expression for maximum applicability of its biological potential. However, most studies have not yet provided such detailed results and the clinical use of Klotho will require further studies in the future.